The Routledge companion to Vsevolod Meyerhold - Pitches, Jonathan, 1968-; Aquilina, Stefan (Routledge theatre and performance companions., 2023)
"The Routledge Companion to Vsevolod Meyerhold brings together a wealth of scholarship on one of the foremost innovators in European theatre. It presents a detailed picture of the Russian director's work from when it first emerged on the modern stage to its multifarious present-day manifestations. By combining an historical focus with the latest contemporary research from an international range of perspectives and authors, this collection marks an important moment in Meyerhold studies as well as offering a new assessment of his relation to today's theatre-making. Its dynamic blend of research is presented in five sections: Histories enlarges on more conventional subjects like the grotesque and biomechanics, to overlooked topics such as Meyerhold's 'failed' projects and his work in film; Collaborations and Connections extends understandings of Meyerhold's well-known collaborative capacities to consider new cultural influences and lesser known working relationships; Sources engages with hitherto untapped material in Meyerhold's oeuvre by reproducing and contextualising previously untranslated primary sources on his work; Practitioner Voices radically extends geographical understandings of Meyerhold's practice by mapping the routes of migration across continents; Meyerhold in New Contexts examines ways in which Meyerhold's work is being applied in a number of contemporary scenarios, such as motion capture, computer-based 3D visualizations and the 'new normal' of digital pedagogy. This is a key resource for students and scholars of European Theatre, acting theory and actor training, as well as for those more broadly interested in the socio-political impact of theatre"--